Grid integration of renewable energy systems - Banerjee, B.; Jayaweera, D.; Islam, Syed (2016)
© Springer International Publishing Switzerland 2016. The percentage of renewable power demand met by renewable power generators is increasing rapidly. This growth is driven by environmental concerns, government policies and decreasing cost of technologies. However, as the penetration of renewable power sources increases, new challenges in system planning and operation are becoming evident. There are short term operational challenges as well as long term planning challenges due to the intermittent nature of renewable power generation primarily from wind and solar photovoltaics. The study of grid integration of renewables is concerned with determining the optimal technical and regulatory framework that can effectively manage the short term and long term challenges of large scale renewable power penetration. Operational challenges of this chapter include maintaining frequency and voltage stability due to intermittency as well as network congestion. Planning challenges include allocating long term capacity credits of wind and solar power generation. Currently, the cost of a number of balancing technologies is expected to play a major role in overall viability of renewable power generation. This includes energy storage, demand side management, and dynamic ratings of assets. Smart grids are expected to provide the platform for utilizing the full potential of renewable power generation as well as balancing the technologies.